2007
DOI: 10.1016/j.ejheart.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levosimendan on coronary artery flow and cardiac performance in patients with advanced heart failure

Abstract: Background: Levosimendan has inotropic and vasodilatory effects. We investigated the effects of levosimendan on coronary flow and associated changes in neurohormonal activation and cardiac performance in patients with advanced heart failure. Methods: Forty-two patients with NYHA III-IV and a left ventricular ejection fraction (EF) 25 ± 6%, were randomised to levosimendan 0.1 μg/kg/min (n = 21) or placebo for 24 h. Before and 24 h after each treatment, we assessed: the maximal velocity (Vmax), time integral (VT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 24 publications
(40 reference statements)
2
36
0
2
Order By: Relevance
“…A recent study [56] has shown that 24 h levosimendan infusion induces improvement in echocardiographic indexes of coronary flow in patients with ADHF. In particular, it increased the maximal velocity and the deceleration time of diastolic coronary flow wave in left anterior descending coronary artery, whereas it reduced BNP levels, pulmonary artery systolic pressure and E/E 0 at greater extent than the placebo treatment.…”
Section: Effects On Right Ventricular Functionmentioning
confidence: 98%
“…A recent study [56] has shown that 24 h levosimendan infusion induces improvement in echocardiographic indexes of coronary flow in patients with ADHF. In particular, it increased the maximal velocity and the deceleration time of diastolic coronary flow wave in left anterior descending coronary artery, whereas it reduced BNP levels, pulmonary artery systolic pressure and E/E 0 at greater extent than the placebo treatment.…”
Section: Effects On Right Ventricular Functionmentioning
confidence: 98%
“…12 Of these benefi cial effects, peripheral vasodilatation is achieved by acting on adenosine triphosphate (ATP)-dependent K + channels. 5 An ischemic reperfusion study has suggested that levosimendan improves myocardial function by limiting the myocardial infarct zone. 13 In another ischemic reperfusion model, however, levosimendan is reported to improve hemodynamic parameters but produces limited decreases in the infarct zone in the absence of coronary collateral.…”
Section: Anti-ischemic Effectmentioning
confidence: 99%
“…Levosimendan treatment produces improvements in cardiac performance and neurohumoral activation in parallel with its positive effects on coronary circulation. 5 These effects result is an increased left ventricular systolic function. 6 Although baseline studies have reported positive results for the effectiveness of levosimendan in acute cardiac failure, 7,8 two recent large studies failed to show a superiority to placebo and dobutamine.…”
Section: Introductionmentioning
confidence: 99%
“…Levosimendan is a calcium sensitizer that increases the contractile force of the myocardium by enhancing the sensitivity of myofilaments to calcium without increasing intracellular calcium concentration [2,3]. It has been reported that levosimendan improves certain aspects of cardiac function and is effective for treating acute cardiac failure [4,5,6]. However, in other studies, levosimendan has not been found to be any more effective for survival than placebo or dobutamine.…”
Section: Introductionmentioning
confidence: 98%